Fixed dose rivaroxaban can be used in extremes of bodyweight: A population pharmacokinetic analysis. (31st August 2020) - Speed, Victoria; Green, Bruce; Roberts, Lara N.; Woolcombe, Sarah; Bartoli‐Abdou, John; Barsam, Sarah; Byrne, Rosalind; Gee, Emma; Czuprynska, Julia; Brown, Alison; Duffy, Sinead; Vadher, Bipin; et al.
Abstract: Background: Emerging safety and efficacy data for rivaroxaban suggest traditional therapy and rivaroxaban are comparable in the morbidly obese. However, real‐world data that indicate pharmacokinetic (PK) parameters are comparable at the extremes of body size are lacking. The International Society of Thrombosis and Haemostasis Scientific and Standardisation Committee (ISTH SSC) suggests avoiding the use of direct oral anticoagulants (DOACs) in patients weighing >120 kg or with a body mass index >40 kg/m 2 and gives no recommendation on the use of DOACs in those <50 kg. Objectives: To generate a population PK model to understand the influence of bodyweight on rivaroxaban exposure from clinical practice data. Method: Rivaroxaban plasma concentrations and patient characteristics were collated between 2013 and 2018 at King's College Hospital anticoagulation clinic. A population PK model was developed using a nonlinear mixed effects approach and then used to simulate rivaroxaban concentrations at the extremes of bodyweight. Results: A robust population PK model derived from 913 patients weighing between 39 kg and 172 kg was developed. The model included data from n = 86 >120 kg, n = 74 BMI >40 kg/m 2, and n = 30 <50 kg. A one‐compartment model with between‐subject variability on clearance and a proportional error model best described the data. Creatinine clearance calculated by Cockcroft‐Gault, with lean bodyweight as the weight descriptor in this equation, was the most significant covariate influencing rivaroxaban exposure. Conclusions: Our work demonstrates rivaroxaban can be used at extremes of bodyweight provided renal function is satisfactory. We recommend that the ISTH SSC revises the current guidance with respect to rivaroxaban at extremes of body size.